Neotectonic control of shelf valley formation on the southern Pernambuco continental shelf - Brazil - Luis Felipe de Melo Tassinari; Tereza Cristina Medeiros de Araújo; José Antônio Barbosa (Ocean and Coastal Research)
Formed during marine regression periods, shelf valleys (SVs) are preterit river flows on the exposed continental shelf. This study investigates the influence of tectonic activity on forming these important morphological features. This research combines bathymetric, magnetometry, and seismic data to analyze the role of tectonic events in SV genesis and positioning. The bathymetric dataset provides information on SV locations and geometries along the continental shelf, whereas the 2D seismic sections illustrate that SVs formed above post-rift faults that reached Quaternary deposits. Aeromagnetic data indicates that the shallow and deep structures of the basement and sedimentary column controlled SV locations and evolution. The multi-data integration demonstrates a strong correlation between neotectonic structures and SV location and geometries from the inner shelf (−25 m) to the shelf break (−55 m). The analysis of the 2D seismic data indicated that high-angle faults, formed under a strikeslip tectonic regime, primarily affected the Middle Miocene deposits beneath the shelf valleys. The formation of “negative flower pattern structures” was identified as a primary structural mechanism that contributed to SV formation. Reactivation events that occurred from the Late Cretaceous onwards, gave rise to these faults, which control SV formation and the capture of preterit drainage on the exposed continental shelf. The SV geometries display straight patterns and abrupt changes in direction (90°) due to the interplay of the NE-SW and NW-SE aligned faults. The results reinforce the importance of considering tectonic activity in the formation and evolution of shelf valleys.